Makroekonomiczne uwarunkowania rozwoju polskiego rynku badań - Idzik, Marcin; Śmiłowski, Eugeniusz (Macroeconomic Conditioning of Development of Polish Research Market, 2006)
A description of changes occurring on the Polish market research of market with regard to macroeconomic transitions in the last decade is presented in this study. Factors influencing the growth of the research market and defining its structure both from the point of view of the client's business structure and used survey techniques are identified. The article shows relations defining the dependency of sales dynamics of the research business on changes of the macroeconomic business outlook. It also makes an attempt to analyse the research market in Poland using methods of spatialtime analogies. A consumer market model in the analysis of the outlook for the research market in Poland is presented.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1107, s. 118-130